(untitled) (Revista Brasileira Multidisciplinar, 2026)
The water quality of small receiving water bodies near urban areas can reflect the increased water demand for multiple uses and urban infrastructure problems, for which information on quality indices is scarce. Thus, this study aimed to evaluate the seasonality and variables that exert the greatest influence on the Water Quality Index (WQI) in the Mumbuca stream, in the urban area of ​​Monte Carmelo/MG. Water samples were collected bimonthly and the variables dissolved oxygen (DO), temperature, pH, thermotolerant coliforms, biochemical oxygen demand (BOD), nitrate, total phosphorus, turbidity and total solids were evaluated and used to calculate the WQI and its classification according to the definitions of the National Sanitation Foundation (NSF). The diagnosis of the seasonality of the WQI-NSF for each monitoring point classified the water quality as average for points M1 and M2 and poor for points M3 and M4. The multivariate analysis showed that the DO variable had a positive effect, while BOD, turbidity, and total nitrate and phosphorus concentrations had negative effects. The results showed that the Mumbuca stream had average and poor IQA-NSF values, evidencing the possible impact caused by human activity and clandestine sewage connections in the storm drainage network in the urban area.